Complete mitochondrial genome of Eurema blanda and phylogenetic relationship with its congener E. hecabe and other pierid butterflies - Yong, Hoi Sen; Song, Sze Looi; Lim, Phaik Eem; Eamsobhana, Praphathip; Suana, I. Wayan (Elsevier, 2017)
Eurema blanda is a member of the hecabe group of pierid butterflies belonging to the subfamily Coliadinae. We report here its complete mitochondrial genome (mitogenome) determined by next-generation sequencing and its phylogenetic relationship with its congener E. hecabe and other pierid butterflies. The whole mitogenome possessed 37 genes and a control region. It had a total length of 15,123ï¿½bp. The start codons ATA and ATC present in E. hecabe were not represented in E. blanda. In both species, the cloverleaf structure of trnS1 lacked the DHU-arm, and trnF lacked the TψC-loop. Molecular phylogeny based on 37 mt-genes reveals close affinity between E. blanda and E. hecabe although not as a sister group. The three subfamilies (Pierinae, Coliadinae and Dismorphiinae) of Pieridae are monophyletic, with Pierinae and Coliadinae forming a clade distinct from that of Dismorphiinae. The complete mitogenome is suitable for studying genetic diversity, systematics and higher-level phylogeny.